Cyclopia: A Rare Congenital Anomaly - Gautam, Uttara; Shrestha, Sandeep; Phuyal, Rajan (Journal of Karnali Academy of Health Sciences, 2023)
Cyclopia is the most extreme form of holoprosencephaly. It is characterized by the failure of the embryonic prosencephalon to properly divide the orbits of the eye into two cavities which results in babies with a single or partially divided eye in a single orbit. We report a case of a 28 years old primigravida who came for medical termination at 25 weeks of gestation and delivered a 600 grams dead female fetus with cyclopia, fetal proboscis, and neurocutaneous marker. Its incompatibility with life makes early diagnosis using ultrasonography and fetal magnetic resonance imaging essential in early management and essential counseling to parents